Permasalahan yang Dialami Lansia dalam Melakukan Penyesuaian Diri di Panti Sosial dan Implikasinya terhadap Layanan Bimbingan dan Konseling (Studi Deskriptif terhadap Lansia di PSTW Sabai Nan Aluih Sicincin) - Fitri Febriani; Syahniar Syahniar; Zikra Zikra (Indonesian Institute for Counseling, Education and Therapy (IICET), 2015)
Changes that occur when entering old age requires a new kind of adjustment, that adjustments to themselves and to the environment. For the elderly who live in social institutions they require the ability to adjust to life in social institutions. In fact there are elderly people who do not have the ability to adapt in the social institutions. This study aims to determine the problems in the elderly make adjustments in social institutions. This research is descriptive. The sample of 31 people. The findings show that 1) 21.75% of elderly have problems in personal adjustment includes adjustments to the physical changes, and adjustments to the psychological condition, 2) 22.81% of elderly have problems in social adjustment includes adjustment of relationships with fellow residents, adjusting relationships with nursing board, adjustment of relationships with family, and adjustments to regulation of social institutions.